Prevalence of overall and specific depressive symptoms : a comparison between athletes and non-athletes - Hlynur Hreinsson 1992- (2022)
Background: The research interest in depressive symptoms among athletes is grown, in accordance with the increased coverage of mental health in athletes. Most studies assessing prevalence rates of clinically significant depressive symptoms use questionnaires as measurement tools to assess depression rates among athletes. Clinical levels of depressive symptoms are determined using predetermined cut-off scores, the issue with the approach is that questionnaires do not differentiate between symptoms thus athletes can report clinically significant depressive symptoms without exhibiting the core symptoms of depression required for a diagnosis (depressed mood or lack of interest). Aims: 1) examine and compare the prevalence of clinically significant depressive symptoms of athletes and a control group of non-athletes. 2) examine and compare the prevalence of individual depressive symptoms among athletes and non-athletes. 3) Examine the percentage of clinically relevant sum scores which do not exhibit either core symptom of depression. Method: The sample consisted of 248 Icelanders living in north-eastern Iceland of which 60 were athletes and 188 were non-athletes. The PHQ-9 was used to assess depressive symptoms. Results: Athletes reported a prevalence of 18.3% compared to 31.2% for non-athletes this difference was marginally non-significant. Athletes reported significantly lower mean score on the PHQ-9 than non-athletes. Non-athletes reported significantly higher prevalence rates of fatigue and sleep problems compared to athletes. Of those with clinically significant sum scores, 41.4% of non-athletes and 27.3% of athletes did not exhibit either core symptom of depression. Conclusion: Findings show that athletes may potentially experience depressive symptoms to a lesser extent than non-athletes. The study of individual depressive symptoms deserves more attention in the literature when considering the number of individuals with clinically significant sum scores who did not exhibit either of the core symptoms of ...